Biomechanical analysis of the underwater phase in swimming starts - Pereira, S. M; Ruschel, C.; Araujo, L. G. (Biomechanics and Medicine in Swimming X, 2006)
This study analyzed, through kinemetry, the underwater phase of the swimming Start. The sample was composed by 4 swimmers of national and state levels. Three VHS video cameras (30Hz) and Signal synchronizer equipment were used. Analyzed variables: maximum depth achieved, time, distance and average velocity of the underwater phase and total Start time in 15 meters. The maximum depth achieved after the entrance in the water had influenced significantly the underwater phase. The average velocity during this phase seems to be the variable which most affects the total start time in 15 meters. Maximum depth achieved and average velocity are important factors to be observed by athletes and coaches, who should look forward to perform best values of those variables in order to improve the execution of swimming Starts.